Group delay investigation of N-order chirping mirrors - Lysak, V.V.; Sukhoivanov, I.A.; Petrov, S.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
We present the numerical calculation of N-order chirping mirrors with chirping both high and low refractive index layers using the transfer matrix method. The group delay and group delay dispersion are investigated for these structures. It is shown that the group delay dispersion is negative and constant at Bragg wavelength for four-order chirping mirrors.